PENGARUH PENDAPATAN ASLI DAERAH TERHADAP BELANJA MODAL DI KOTA PEMATANG SIANTAR - Malau, Eve Ida; Sumaizar, Sumaizar (UNIKA Santo Thomas, 2023)
ABSTRACT This research aims to determine and analyze the effect of original local revenue (PAD) on the capital expenditure of Pematang Siantar city. The data used in this research is time series data regarding original local revenue and capital expenditure of Pematang Siantar city in 2011-2022. Data analysis methods consist of simple linear regression analysis, t-test, and analysis of the coefficient of determination. From the simple linear regression analysis is obtained Y = 25.019 + 1.276X.. The constant value of 25.019 means that if the original local revenue is constant, the capital expenditure of Pematang Siantar city is 25.019. The original local revenue regression coefficient shows a positive effect on capital expenditure of 1.276. From the results of the t-test is explained that t count > t table (2.054 > 1.812) where original local revenue affects capital expenditure. From the analysis of the coefficient of determination is known that original local revenue influences the capital expenditure of Pematang Siantar city by 29.7% and the other 70.3% is influenced by other factors other than original local revenue.